COMPARISON OF THE EFFECT OF FOREIGN DEBT ON ECONOMIC GROWTH OF INDONESIA IN THREE PERIODS OF GOVERNMENT - Endang Kusdiah Ningsih; Esty Naruliza; Asma Mario (S1 Accounting Department, Faculty of Economic, Universitas Pamulang., 2018)
This purpose of this articel is to determine the ratio of the effect of foreign debt on economic growth. Since the reign of the Old Order up to the reign of the Reform Order to date, the Indonesian government has always done debt (overseas loans). So as if the growth that accomplished by the Indonesian economy each year can not be separated from foreign debt.The data used are secondary data obtained from the Central Bureau of Statistics and Bank Indonesia. The analysis technique to be used is Quantitative Descriptive Method. The results of hypothesis test show that the effect of foreign debt on economic growth only during the Reform Order.